Competitive strategies and organizational performance in ship management - Panayides, Photis (My University, 2003)
Ship management has been characterized by strong competition that resulted in structural changes in the industry, with the bigger companies merging or acquiring smaller ones in an effort to remain competitive. Competitiveness, however, may also be attained through the formulation and implementation of competitive business strategies that will improve performance. The aim of this paper has been to empirically examine the competitive strategy-performance relationship in the context of ship management companies. The findings suggest that there is a positive relationship between pursuing competitive strategies and company performance in ship management. Companies that apply competitive strategies are more likely to be high performers. The strongest influences on performance seem to be achieving economies of scale, differentiation (in particular through a wider range of services offered) and market-focus and competitor-analysis. It is suggested that high performers are more likely to pursue a combination of the generic strategies rather than pursuing one of the generic strategies in isolation
Keywords: Shipping; Ships; Harbors; Management; Transportation; Competitiveness (Economics)